Benefícios econômicos a partir da participação em esquemas associativos: o caso das quebradeiras de coco babaçu do povoado Ludovico, município de Lago do Junco-Maranhão - Ruiz, Javier David Sosa (2009)
The region of the “Médio Mearim” in the Brazilian state of Maranhão, it is the epicenter of one of the strongest social movements - it is linked to “agroextrativismo”, in that nation. The “quebradeiras de coco babaçu” –women whose main activity is to break the babassu coconut and it is ratified as traditional population, have built an associative system that includes: a cooperative that produces and exports oil from organic babassu; a team of technical assistance, which channels its demands and market demand for products with the coconut’s value; a group of young people which trains itself constantly, seeking to transform and fully exploit the coconut; a group of women who has built a soap factory of babassu, which is also exported; finally, a movement that brings together not only as a whole the region but all the “quebradeiras” - and its more than four hundred thousand families in four states: Pará, Piauí, Tocantins and Maranhão. This study fits into the context of a region where the fight for rights to land triggered a vision of collective work and conservation of babassu. This project also seeks to implement the culture of total use of coconut. It has, as well, the objective of describing how this platform organizations benefit -socially and economically, the “quebradeiras” and their families. All this is carried out featuring the current stage of network capital formed there. Because of this, the methodology includes: periodic field visits for a year, in order to take data and to evaluate the formation of income. It contents also, semistructured interviews with key informants and leaders of organizations. The agro extractive system of babassu coconut -which seems to be so studied, still has many aspects to describe. As this study shows, the organizations’ role goes far ahead of their objectives getting more than just protecting the babassu: they improve the families’ income; moreover, they fight for the rights of “quebradeiras” to maintain an identity, while slowly they open a path to more business-related vision to add value to products of coconut babassu.